2016
DOI: 10.1002/cpdd.237
|View full text |Cite
|
Sign up to set email alerts
|

A Phase 1 Dose‐Escalation Study of ASP2409, a Selective T‐Cell Costimulation Inhibitor, in Stable Rheumatoid Arthritis Patients on Methotrexate Therapy

Abstract: ASP2409 represents a new class of CTLA4-Ig molecules with higher binding avidity and selectivity to CD86. This first-in-human study was to assess the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics of ASP2409 in stable rheumatoid arthritis patients on methotrexate therapy with a randomized, double-blind, placebo-controlled dose-escalation study design. Patients were enrolled and randomized in each of 8 dose-escalation cohorts ranging from 0.001 to 3.0 mg/kg to receive either ASP2409 or placeb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…In addition, remarkable attention has been paid to explore potential efficacy of a new monoclonal antibody. Zhang et al assessed the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics of ASP2409 in the first‐in‐human study with higher binding avidity and selectivity to CD86 184. Furthermore, even in clinical trials, more types of nanomedicines will be found to reduce dose and frequency of dosing to achieve minimal adverse reactions and maximal treatment outcomes.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…In addition, remarkable attention has been paid to explore potential efficacy of a new monoclonal antibody. Zhang et al assessed the safety, tolerability, pharmacokinetics (PK), and pharmacodynamics of ASP2409 in the first‐in‐human study with higher binding avidity and selectivity to CD86 184. Furthermore, even in clinical trials, more types of nanomedicines will be found to reduce dose and frequency of dosing to achieve minimal adverse reactions and maximal treatment outcomes.…”
Section: Conclusion and Prospectsmentioning
confidence: 99%
“…ASP2409 represents a new class of CTLA4-Ig molecules with higher binding avidity and selectivity to CD86. A phase I trial of ASP2409 in RA showed that this agent is tolerable and further clinical trials are pending [20].…”
Section: Cd80 and Cd86 Inhibitionmentioning
confidence: 99%